Genetic Differentiation and Adaptability of Teak (Tectona grandis L.f.) Meta-Population in India - Vaishnav, Vivek; Ansari, Shamim Akhtar (Plant molecular biology reporter, 2018)
The genetic differentiation of teak meta-population in India was investigated in relation to geographical and climatic variations employing dominant ISSR markers followed by Bayesian statistical analysis to understand adaptability of the species. The analysis based on 290 teak genotypes representing 29 locations of its natural distribution and 43 ISSR loci exhibited an insignificant structure and low 2.76% LD (≥ 0.1 R 2 values, p < 0.001) in teak meta-population. The genetic and geographical variables despite acting independently with each other resulted in three sub-population clusters in the meta-population. The geographical barrier played a significant role in direction/restriction of gene flow. The integration of spatial/climatic variables altered the clustering pattern of the teak meta-population with signature of the adaptation to the temperature and longitudinal gradients that was also verified by the similar adaptation pattern of meta-population towards predicted global climate modeling for year 2050. The findings can help tackle the sustainable management and conservation of the species and its survival quotient in threat of changing climatic conditions.